The Nutritional Issue of Older People Receiving Home-Delivered Meals: A Systematic Review - Fleury, Ségolène; Tronchon, Paul; Rota, Juliane; Meunier, Charlotte; Mardiros, Oliver; Van Wymelbeke-Delannoy, Virginie; Sulmont-Rossé, Claire (Frontiers in Nutrition, 2021)
Background. Setting up a home-delivered meal service often allows older people suffering from physical and/or cognitive disabilities to stay at home. However, older people who delegate their food activities (food purchasing, cooking…) have been reported to have a worse nutritional status than people who take care of their food activities. In this context, we will conduct a systematic review of all studies related to the nutritional issue in home-delivered meal older recipients. Methods. In June 2020, we searched 3 databases (Pubmed, Web of Science, EMBASE) to identify studies from all years on older adults at home and receiving home-delivered meals services (population). The following outcomes were considered: nutritional status (Body Mass Index, weight, undernutrition) and nutritional intake. Any nutritional intervention, comparator and study design were relevant for inclusion. Results. Forty-eight original studies met the inclusion criteria, most of them being published after 2000 (n=34) and undertaken in the USA (n=32). The selection includes 30 cross-sectional and 18 longitudinal studies. The main findings of this review are the following: 1) home-delivery meals older recipients are at high risk of undernutrition; 2) providing home-delivery meals may improve the nutritional status and nutrient intake; 3) this improvement is even higher when the home-delivery meal service is improved, for instance by providing dietetic counselling, adding supplementary snacks/meals, or enriched food. However, even an improved service does not allow all the older recipients meeting their recommended nutritional allowance. Conclusion. This review reveals a need to further develop strategies allowing home-delivery meals’ older recipients to fulfill their nutritional needs. From a methodological point of view, there is a need to describe in more detail the home-delivered services provided to studies’ participants to better consider meal frequency and meal content in the results.